A new technique to correct the iris shading of ocular prosthesis - Nafij Bin Jamayet (2018)
Background: The exact matching shade of iris selection is difficult. Re-procedure of iris shade selection mostly occurs. Method: This article suggests a technique to correct the shade of iris for saving the laboratory time and improving the esthetic outcome. Result: The correction by punch out the old iris in ocular prosthesis with keeping the same size and location. Replace the new shading iris, cover with heat cure clear acrylic resin and follow the conventional procedure. Conclusion: Our technique helps us to correct the error of ocular prosthesis in an easy way by reducing time and materials. © 2013 Japan International Cultural Exchange Foundation and Japan Health Sciences University.